(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Diabetic polyneuropathy (DPN) has a significant positive correlation with poor glycemic control (HbA1c ≥7%). The clinical, biochemical and electrophysiological parameters of DPN in Bangladeshi citizens have not yet been explored elaborately Objective: The purpose of the study was to detect and categorize status of glycemic control of Bangladeshi people and to analyze its impact on clinical severity of DPN using Toronto Clinical Scoring System (TCSS) and electrophysiological severity by modified Michigan diabetic neuropathy score (MDNS). Methodology: This observational study was carried out on diabetic patients having probable DPN by purposive sampling, attending Neurology OPD of Dhaka Medical College Hospital, Dhaka, Bangladesh and Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine & Metabolic Disorder (BIRDEM) Hospital, Dhaka, Bangladesh from July 2014 to June 2016. Clinical parameters were recorded and DPN was graded as “no neuropathy”, “mild”, “moderate” and “severe” neuropathy by the Toronto Clinical Scoring System (TCSS). A standard nerve conduction study was performed on each patient and electrophysiological grading according to modified Michigan diabetic neuropathy score (MDNS) was done. Diabetic status of patients was classified into “controlled” (HbA1c <7.0%) and “uncontrolled” (HbA1c ≥7.0%) groups and HbA1c level and the clinical & electrophysiological severity scores were compared and were analyzed. Results: Mean age of the patients was 57.2±9.37 years. 51.0% cases were males and 49% cases were females. The mean HbA1c in the study population was 7.6±0.94% and 56.0% patients had HbA1c≥ 7% .Motor nerve conduction studies revealed that both CMAP amplitudes and MNCV in the ulnar, peroneal and tibial nerves were reduced significantly in patients of uncontrolled (HbA1c≥7%) DM (p<0.001). Sensory nerve conduction studies revealed significant reduction in SNAP amplitudes of median and ulnar sensory and sural nerves in the uncontrolled group (p<0.001). Electrophysiologically, 65.43% patients had mixed sensory-motor neuropathy (p<0.00001). Clinically severe DPN patients were higher (45.2%) within the uncontrolled (HbA1C ≥7%) group (p<0.00001). Similarly, severity in electrophysiological grading was more in patients with uncontrolled DM (48.8%) (p<0.00001). Conclusions: Neuropathic severity, either clinically or electrophysiologically, was associated with higher values of HbA1c. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 177-184